Changes of carbohydrate contents in curcuma alismatifolia Gagnep. Affected by red light - A. Chidburee (2018)
The effects of red light on carbohydrate content in Curcuma alismatifolia Gagnep. were studied. Plants grown under two artificial light sources: T1) red light fluorescent lamp (Philips TLD 36W/15; 632-660 nm) and T2) cool daylight source (Philips TLD 36W/865; 405-812 nm) at 27±2°C, 70-80% RH and 60 μmol m-2s-1PAR of light intensity compared with growing under natural condition (T3). Each plant were supply with 100 ml of nutrient solution comprised of 200 mg N, 50 mg P, 200 mg K, 65 mg Ca, 20 mg Mg, 0.22 mg B, 0.54 mg Mn, 0.26 mg Zn, 0.04 mg Mo and 0.45 mg Fe per litre, three times a week. The starch content in new rhizome of plants growing under red light was the lowest. Total soluble sugar, fructose, glucose and sucrose of plants growing under natural light were the highest. The contents of starch and total soluble sugar in storage roots of plant grown under natural light were the highest.